2020
DOI: 10.1039/c9fo02667c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of collagen peptides from skate (Raja kenojei) skin on improvements of the insulin signaling pathway via attenuation of oxidative stress and inflammation

Abstract: It has been well established that hepatic insulin signaling is significantly affected by the antioxidative status of the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…Marine‐based collagen scaffold has applications in bone (TE), [ 74–76 ] wound healing, [ 77 ] food, and nutraceuticals and nutricosmetic. [ 78–82 ]…”
Section: Source Of Collagenmentioning
confidence: 99%
“…Marine‐based collagen scaffold has applications in bone (TE), [ 74–76 ] wound healing, [ 77 ] food, and nutraceuticals and nutricosmetic. [ 78–82 ]…”
Section: Source Of Collagenmentioning
confidence: 99%
“…Other studies have shown the anti‐hyperglycemic effect to be even more pronounced in a chronic setting, with the lowest dose used being 100 mg kg −1 bodyweight. [ 41,48,68,87 ] Furthermore, all in vivo studies investigating the satiating effect of FPH have shown a decrease in bodyweight or a reduction in weight gain. [ 39,65,66,88 ] These findings are very encouraging, given the wide methodological variation between studies discussed previously.…”
Section: Discussionmentioning
confidence: 99%
“…[ 94,95 ] A trial involving skate skin also showed a reduction in bodyweight and fat mass. [ 87 ] Generally speaking, human trials involving FPH have been reasonably successful with the exception of results from a single cod protein hydrolysate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the Keap1/Nrf2‐ARE pathway is the main target for studying the mechanism of oxidative damage and screening antioxidant drugs (Cuadrado et al., 2019; Mimura & Itoh, 2015). It was demonstrated that the antioxidant peptides, curcumin, and L‐carnitine could activate the Keap1/Nrf2‐ARE pathway, reducing the oxidative damage of liver cells (Chan et al., 2018; Woo et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Magnolol of 20 mg/kg increased the levels of p‐PI3K and Nrf2 by about three times in the liver of alcohol‐induced mice, suggesting that it could prevent liver damage by activating PI3K/Nrf2 signaling pathways (X. Liu et al., 2019). The collagen peptides obtained from skate skin ( Raja kenojei ) could protect the liver from injury by increasing the antioxidative status via PI3K/AKT and Nrf2/ARE signaling pathways (Woo et al., 2020). The MAPKs mainly include extracellular regulated protein kinases (ERK), c‐Jun N‐terminal kinase (JNK), and p38, all which related to inflammation, apoptosis, and growth.…”
Section: Introductionmentioning
confidence: 99%